Understanding Role of Stunting Toddler Volunteers in Batu, Indonesia - Nurul Aini; Aini Alifatin; Ika Rizki Anggraini (Humanistic Network for Science and Technology (HNST), 2021)
WHO determined the stunting tolerance (short-height), maximally 20% or a fifth of the whole toddler numbers. The initial report in 2018 showed 1,237 toddlers suffering stunting from the whole 14,285 toddlers in Batu. This research aims to describe the role of stunting toddler volunteers to accompany families with toddlers in Javanese Batu. This was a qualitative research with a phenomenological approach. The data were collected by in-depth interview. The data analysis results consisted of five research themes. They were: (a) the volunteers accompany the families by firstly detecting the stunting toddler indication, (b) the main focus of the volunteers was educating them about toddler-nutritious meals, (c) all participated volunteers were women, (d) the volunteers facilitated the communication and consultation for all the guided families, (e) their motivation to be volunteers was a social spirit to help each other and contribute to the community and social life. Generally, the volunteers had accompanied the family excellently. The given education by the volunteers consisted of toddler meal and nutrition and strategies to instill excellent behaviors for both the children and families. Keywords: stunting; toddlers; volunteers; role